DIGITAL ECONOMY AND ITS IMPACT ON BUSINESS AND MEDICINE TRANSFORMATION IN 2024: UZBEKISTAN'S EXPERIENCE AND ACHIEVEMENTS IN DIGITAL TRANSFORMATION - Mirzarakhimova A. B. (Modern American Journals, 2025)
The digital economy has a large-scale impact on traditional forms of doing business, employment and social institutions. The article discusses the key areas of digital transformation, including the role of the Internet, the development of digital technologies in medicine, the impact on consumer behaviour and the global economy. It also gives examples of modern technological solutions and start-ups changing the landscape of industries. Special attention is paid to Uzbekistan's achievements in digitalisation and innovation.
Keywords: Digital economy, threats and risks to sustainable development, economic growth, state regulation of the economy, scientific and technological progress.